The Strategic Role of Policy in Advancing Educational Management - Heriman; Muhammad Saparuddin; Muhlis; Abdunnur; Muhammad Amir Masruhim; Laili Komariyah (Journal of Educational Management Research, 2026)
Education serves as a fundamental pillar in national development, and effective policies play a crucial role in strengthening social, economic, and cultural structures. In Indonesia, various educational policies such as the 12-Year Compulsory Education Program and the School Operational Assistance (BOS) have been introduced to expand access and enhance the quality of learning. The purpose of this study is to examine the role of educational policy within the management of Indonesia’s education system, assess its influence on educational quality, and identify key challenges that arise during policy implementation. This research employs a qualitative descriptive method, drawing on policy reviews, document analysis, and findings from previous empirical studies related to educational policy and management. The results indicate that while national policies have contributed to broader access to education, significant disparities continue to emerge between urban and remote areas, particularly in terms of infrastruct